2016
DOI: 10.1093/mnras/stw1519
|View full text |Cite
|
Sign up to set email alerts
|

Peculiar double-periodic pulsation in RR Lyrae stars of the OGLE collection – I. Long-period stars with dominant radial fundamental mode

Abstract: We present the discovery of a new, peculiar form of double-periodic pulsation in RR Lyrae stars. In four, long-period (P > 0.6 d) stars observed by the Optical Gravitational Lensing Experiment, and classified as fundamental mode pulsators (RRab), we detect additional, low-amplitude variability, with period shorter than fundamental mode period. The period ratios fall in a range similar to double-mode fundamental and first overtone RR Lyrae stars (RRd), with the exception of one star, in which the period ratio i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 41 publications
5
39
0
Order By: Relevance
“…In addition, the low-amplitude double-mode variables found by Smolec et al (2016) with a dominant fundamental mode and long periods fall roughly in the region of Oo III variables. Most of these double-mode pulsators can be described using linear pulsation models with very high metallicity (around -0.5 dex).…”
Section: Comparison With Bulge Gcs and Physical Parametersmentioning
confidence: 82%
See 1 more Smart Citation
“…In addition, the low-amplitude double-mode variables found by Smolec et al (2016) with a dominant fundamental mode and long periods fall roughly in the region of Oo III variables. Most of these double-mode pulsators can be described using linear pulsation models with very high metallicity (around -0.5 dex).…”
Section: Comparison With Bulge Gcs and Physical Parametersmentioning
confidence: 82%
“…The period ratio of this additional peak and the dominant mode is 0.720, therefore it lies in a region of the Petersen diagram (see fig. 1 in Smolec et al 2016) where the aforementioned double-mode pulsators occur. We did not detect any signal at the combination frequency of the dominant mode and the additional signal ( f x ).…”
Section: Comparison With Bulge Gcs and Physical Parametersmentioning
confidence: 99%
“…Therefore, some of the stars in our sample might have been stripped from NGC 6441 in the past and have mixed with the bulge field population of RR Lyrae stars. In addition, one of these stars is a candidate for the double-mode variables found by Smolec et al (2016), which, based on stellar pulsation models, have a high metallicity despite the low metallicity determined using photometric data. After a careful analysis of the Fourier spectra of the remaining four stars, none of them shows any sign of a double-mode behavior.…”
Section: Possible Contaminationmentioning
confidence: 98%
“…Petersen diagrams (Petersen 1973) where the period ratios of mixed-mode Cepheids are plotted versus the longer period are very useful tools to study the properties of these stars. Combined with the huge amount of data provided by the OGLE microlensing survey , they led to numerous discoveries in recent years for both Cepheids and RR Lyrae stars (e.g., Coppola et al 2015;Smolec et al 2016;Prudil et al 2017). 1 A similar number of 1O/2O double-mode Cepheids (that are not relevant for this paper) have also been discovered: CO Aur and V1048 Cen have been known for a long time; V2157 Sgr, V767 Sgr, V363 Cas have been reported by Hajdu et al (2009), and several more stars have been identified by e.g., Soszyński et al (2011); ; Khruslov (2013); Khruslov & Kusakin (2016) in large scale photometric surveys.…”
Section: Introductionmentioning
confidence: 99%